Literary theory : an anthology - Rivkin, Julie; Ryan, Michael, 1951- (2017)
"Covers all the major schools and methods that make up the dynamic field of literary theory, from Formalism to Postcolonialism."--
Part One: Russian formalism -- Part Two: Structuralism, Linguistics, Narratology -- Part Three: Phenomenology, Reception, Ethics -- Part Four: Post-Structuralism -- Part Five: Psychoanalysis and Psychology -- Part Six: Marxism, Critical Theory, History -- Part Seven: Gender Studies and Queer Theory -- Part Eight: Ethnic, Indigenous, Postcolonial, & Transnational Studies -- Part Nine: Cognition, Emotion, Evolution, Science -- Part Ten: Animals, Humans, Places, Things.
Includes bibliographical references, glossary, and index.
Keywords: Literature -- Philosophy; Literature -- History and criticism -- Theory, etc